Multicolour synthesis in lanthanide-doped nanocrystals through cation exchange in water - Sanyang Han (Nature Portfolio, 2016)
De novosynthesis is the primary way to tune the emission colour of lanthanide-doped upconversion nanocrystals. Here, the authors introduce post-synthetic cation exchange as a strategy to access multiple colours of luminescent nanocrystals, preserving the size and morphology of the original template.